Randomized trial of an intervention to improve blood pressure control in stroke survivors (2020)
BACKGROUND: We conducted the first-of-its kind randomized stroke trial in Africa to test whether a THRIVES (Tailored Hospital-based Risk reduction to Impede Vascular Events after Stroke) intervention improved blood pressure (BP) control among patients with stroke. METHODS AND RESULTS: Intervention comprised a patient global risk factor control report card, personalized phone text-messaging, and educational video. Four hundred patients recruited from 4 distinct medical facilities in Nigeria, aged ≥18 years with stroke-onset within one-year, were randomized to THRIVES intervention and control group. The control group also received text messages, and both groups received modest financial incentives. The primary outcome was mean change in systolic BP (SBP) at 12 months. There were 36.5% females, 72.3% with ischemic stroke; mean age was 57.2±11.7 years; 93.5% had hypertension and mean SBP was 138.33 (23.64) mmHg. At 12 months, there was no significant difference in SBP reduction from baseline in the THRIVES versus control group (2.32 versus 2.01 mmHg, P=0.82). In an exploratory analysis of subjects with baseline BP >140/90 mmHg (n=168), THRIVES showed a significant mean SBP (diastolic BP) decrease of 11.7 (7.0) mmHg while control group showed a significant mean SBP (diastolic BP) decrease of 11.2 (7.9) mmHg at 12 months. CONCLUSIONS: THRIVES intervention did not significantly reduce SBP compared with controls. However, there was similar significant decrease in mean BP in both treatment arms in the subgroup with baseline hypertension. As text-messaging and a modest financial incentive were the common elements between both treatment arms, further research is required to establish whether these measures alone can improve BP control among stroke survivors